Afirmatywny charakter parodii w La puppé Timothy’ego Greenberga - Sulejewska, Justyna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2014)
The article is an interpretation of La puppé by Timothy Greenberg seen as non-standard, approving form of parody. The analysis begins with a reminder of attributes of this type of stylization, and then comparision of Greenberg’s film with Chris Marker’s La Jetée. No distinct criticism or polemic leads to theory, that the aim of La puppé is to reveal illusive nature of film language.